A designer's research manual : succeed in design by knowing your clients and what they really need. - Visocky O'Grady, Jenn, ....-; Visocky O'Grady, Ken, ....- (Beverly : Rockport, 2009)
Doing research can make all the difference between a great design and a good design. Most experienced designers would quantify this "legwork" with the term research. By engaging in competitive intelligence, customer profiling, color and trend forecasting, etc., designers are able to bring something to the table that reflects a commercial value for the client beyond a well-crafted logo or brochure. Although scientific and analytical in nature, research is the basis of all good design work. This book provides a comprehensive manual for designers on what design research is, why it is necessary, how to do research, and how to apply it to design work. As designers embrace research methodologies, they share a common vernacular with their clients, and establish respect as idea people. In an increasingly crowded marketplace, embracing research practices will ensure a continued viable role for designers in business. No other books address this issue for student and professional graphic designers. Books on how to do research are usually aimed at writers, business marketers, and scientists. The ability to execute effective research methods is as important to a career in graphic design as the ability to build a grid or layout a page. Understanding the needs of the client and the client's market are essential components of creating value.